The effect of retained austenite on austenite reversion behavior and corresponding mechanical properties of Ti–Mo precipitation hardening stainless steels - Chih-Yuan Chen; Iting Chiang; Yung-Chang Kang (Journal of Materials Research and Technology)
Although the ageing process is the most important metallurgical process influencing the austenite reversion reaction, the role of retained austenite existing after cryogenic treatment on austenite reversion transformation is still not fully explored. Therefore, via different cooling modes, i.e. water quenching (WQ), air cooling (AC), and furnace cooling (FC), applied after austenitization treatment, different amounts of retained austenite, namely 0.3 % (WQ), 0.5 % (AC), and 1.2 % (FC), were formed in the martensite matrix of Ti–Mo precipitation hardening stainless steels (PHSSs). Interestingly, even under the same ageing treatment condition, i.e. 520 °C for 4 h, the amount of reverted austenite that formed in Ti–Mo PHSSs strongly depended on the cooling rate used. For instance, according to EBSD phase maps, the reverted austenite contents were 24.7 %, 15.0 %, and 9.4 % in the steel specimens cooled by FC, AC and WQ, respectively. Therefore, a positive correlation was found between retained austenite and reverted austenite after comparison of the overall EBSD analysis results. In addition, it was found that the strength and ductility trade-off relationship was improved in steel samples subjected to the slow cooling treatment, as numerous η-Ni3Ti precipitates and larger amounts of reverted austenite formed simultaneously during the ageing treatment.